Association between maternal cadmium exposure and preterm birth: a meta-analysis. Issue 3 (4th March 2022) - Asefi, Yaser; Gohari Mahmoudabad, Arezoo; Habibian Sezavar, Ahmad; Mirshahvaladi, Shahab; Abyadeh, Morteza; Abyareh, Mostafa
ABSTRACT: The association between Cadmium and the risk of preterm birth (PTB) has remained controversial. A number of studies found a positive correlation between maternal Cd exposure and PTB; however, there are conflicting reports about this correlation. Therefore, herein we performed this meta-analysis to examine the association between maternal Cd exposure and the risk of PTB. A systematic search was conducted through PubMed, Scopus, Embase and OpenGrey from inception to May 2020 to find all eligible studies. Odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were used to examine this correlation. A random-effects model was applied in this meta-analysis due to significant statistical heterogeneity among included studies. Overall, 10 eligible studies met the inclusion criteria and were included in our analysis, and results of the present meta-analysis indicated that maternal cadmium exposure is associated with the risk of PTB (OR = 1.32; 95% CI = 1.08–1.61). This meta-analysis suggests that maternal Cd exposure might be associated with the risk of PTB. Yet, large prospective studies from different ethnic populations which consider other influencing parameters are still required to confirm this finding.